Meta-analysis: Vidian Canal Length, Types, Dehiscence, and Relationship to Medial Pterygoid Plate - Santhosh Kuriakose; A. K. Nuveen; Sanjaykumar B. Revankar; Balakrishna Shetty; Sweekritha Shetty (Wolters Kluwer Medknow Publications, 2024)
Vidian canal (VC) as an anatomical landmark directs endoscopic approaches to the petrous carotid artery and the anteromedial part of the cavernous sinus, facilitating precise surgical access to these intricate regions. The objectives of this meta-analysis were to determine the normal range, pooled averages of VC length, and distance between VC and foramen rotundum (FR); to evaluate the proportion of different types of VC and proportion of dehiscent VC; and to report the relation of VC to medial pterygoid plate (MPP). Embase, Pubmed Central, and other databases were searched for the published articles reporting length, types, dehiscence of VC, relationship with MPP, distance between VC and FR. Prevalence data from individual study were tabulated, and 95% confidence intervals (CIs) were computed. A total of 203 studies were identified from the search. Excluding duplicates, 190 studies were screened for eligibility and 35 articles were selected. Excluding four studies for differential reporting of outcomes, 31 studies were considered for qualitative and quantitative analyses. Sixteen studies reported the length of VC. There was significant heterogeneity indicating variability in effect estimates across studies and this variability was due to difference between study population rather than random variation. The pooled average length of the VC was 14.93 (95% CI: 13.60-16.26). The pooled prevalence of Type 1, 2, and 3 VC was 31% (95% CI: 22%-40%), 43% (95% CI: 34%-51%), and 24% (95% CI: 14%-33%), respectively. The pooled prevalence of VC medial to MPP and on the same plane as that of MPP was 46% (95% CI: 25%-68%) and 48% (95% CI: 29%-67%), respectively.